Ryzyko podatkowe jako kryterium wyboru formy opodatkowania dochodu - Poszwa, Michał (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
In Polish law there are different rules of incomes taxation of personal partnership and capital companies. Different status is very controversial. It is necessary to include tax risk in tax management. There is a problem of different importance of risk in income taxes which appears whether the different charging of both kinds of companies disturbs in the wide range the rules of a competition. The final decision about the form of incomes taxation is very risky. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 355-362